Sosialisasi Pemilahan Dan Pengelolaan Sampah Untuk Meningkatkan Karakter Peduli Lingkungan Pada Siswa Di MIS Halwani Gebang, Langkat, Sumatera Utara - Tuti Rezeki Awaliyah Siregar; Dian Anggeraini; Fahrunnisa Fahrunnisa; Wardati Khumairah Rusydi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This Community Service activity is carried out with the aim of implementing the Tri Dharma of Higher Education. This activity was carried out at MIS Halwani Gebang, Langkat, North Sumatra. The implementation of the activities includes the delivery of material regarding Introduction to Waste Sorting and Management, the Practice of Managing Organic Waste into simple compost and inorganic waste into useful crafts for students.